Multiple SNPs downregulate gene expression of Matrix Metallopeptidase 2 in MCF7 breast cancer cells - Ahmad Suhaimi, Shafinah; Choy, Chan Soon; Pei, Chong Pei; De Ming, Chau; Saad, Norazalina; Rosli, Rozita (Universiti Putra Malaysia Press, 2024)
Introduction: On a global scale, breast cancer contributes the highest cancer-related deaths in women due to metastasis which renders the treatments ineffective and non-targeted. The members of Matrix Metallopeptidases, particularly Matrix Metallopeptidase 2 (MMP2), are among the key players in breast cancer metastasis. In most cases, MMP2 was markedly upregulated and linked to poor prognosis. In a previous study, in silico analyses revealed that several coding single nucleotide polymorphisms (SNPs) of MMP2 were shown to reduce gene expression and mRNA stability of MMP2 in Malaysian breast cancer patients. Therefore, to validate the in silico predictions, the objective of this study was to determine the effects of multiple coding SNPs of MMP2 on the gene expression and mRNA stability of MMP2 in breast cancer cells. Methods: In the current study, breast adenocarcinoma MCF7 cells were transfected with MMP2 wild type and variant containing the coding SNPs. After confirmation of transfection by DNA sequencing, the gene expression level of MMP2 was evaluated by quantitative reverse transcription polymerase chain reaction (RT-qPCR) whereas mRNA stability of MMP2 was determined following treatment with actinomycin D. Results: MMP2 wild type and variant were successfully transfected in MCF7 cells based on sequencing and PCR analysis. It was found that the presence of coding SNPs lowered the gene expression level of MMP2, but not the stability of MMP2 mRNA. Conclusion: This study supports the in silico effects of MMP2 coding SNPs on its gene expression in an in vitro model.